Arduino-based Automatic Greeting with PIR Sensor at Angkringan Mukti Kebumen - Benedi, Juri; Tommy Risky Pratama; Linda Noviasari (Politeknik Piksi Ganesha Indonesia, 2023)
A waiter is a team member in a restaurant or store responsible for welcoming new arrivals or seeing off departing customers, particularly at the main entrance of the establishment. Currently, the process of welcoming customers relies entirely on human workers, which consumes both time and effort. Therefore, an automated welcoming system is needed to enhance efficiency in terms of time and energy. In this study, the research and development method is employed. The automated welcoming system is built on Arduino technology, involving the use of PIR sensors, Arduino Uno R3, DFPlayer, and a Speaker. During the testing of this product, PIR sensors are utilized as human motion detectors. Arduino Uno R3 functions as the brain of the system, receiving data from the PIR sensors. When the first PIR sensor detects motion, Arduino Uno R3 activates the DFPlayer to play sound through the Speaker. If the second PIR sensor detects motion, the first PIR sensor is turned off for 3 seconds. This product has the capability to detect motion up to a maximum distance of 3 meters.